1999
DOI: 10.1590/s0100-879x1999001000015
|View full text |Cite
|
Sign up to set email alerts
|

Atropine and ODQ antagonize tetanic fade induced by L-arginine in cats

Abstract: Although it has been demonstrated that nitric oxide (NO) released from sodium nitrite induces tetanic fade in the cat neuromuscular preparations, the effect of L-arginine on tetanic fade and its origin induced by NO have not been studied in these preparations. Furthermore, atropine reduces tetanic fade induced by several cholinergic and anticholinergic drugs in these preparations, whose mechanism is suggested to be mediated by the interaction of acetylcholine with inhibitory presynaptic muscarinic receptors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In cats it has been shown that tetanic fade induced by NO depends on the action of gas at the presynaptic level; it might increase acetylcholine release from motor nerve terminals, with a consequent activation of inhibitory presynaptic muscarinic receptors (15). Such mechanism might explain the reduction in R values obtained with NO at 50 Hz, but not the increase in R values recorded with NO at 5 Hz.…”
mentioning
confidence: 94%
“…In cats it has been shown that tetanic fade induced by NO depends on the action of gas at the presynaptic level; it might increase acetylcholine release from motor nerve terminals, with a consequent activation of inhibitory presynaptic muscarinic receptors (15). Such mechanism might explain the reduction in R values obtained with NO at 50 Hz, but not the increase in R values recorded with NO at 5 Hz.…”
mentioning
confidence: 94%
“…This suggests that the effects of NO are mediated by activation of guanylyl cyclase. This hypothesis is supported by results from similar studies showing that ODQ, a guanylyl cyclase blocker, antagonizes the effects induced by NO in neuromuscular preparations of cats or rats (11,14).…”
Section: -Aminopyridine Inhibits the Neuromuscular Effects Of Nitricmentioning
confidence: 53%
“…These effects had their origin at the presynaptic level, as previously shown in 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 6 7 8 9 0 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 % 50 0 -25 25 -50 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 2 3 4 5 1 Figure 2). Therefore, we propose that the effects of L-arginine depend on its metabolism by NOS to produce NO, thereby acting on motor nerve endings (14). Furthermore, current research shows that 8-Br-cGMP (18 µM) induced effects similar to L-arginine ( Figure 2).…”
Section: -Aminopyridine Inhibits the Neuromuscular Effects Of Nitricmentioning
confidence: 66%